The Global Sink of Available Potential Energy by Mesoscale Air‐Sea Interaction. (21st October 2020) - Bishop, Stuart P.; Small, R. Justin; Bryan, Frank O.
Abstract: The thermal component of oceanic eddy available potential energy (EPE) generation due to air‐sea interaction is proportional to the product of anomalous sea surface temperature (SST) and net air‐sea heat flux (SHF). In this study we assess EPE generation and its timescale and space‐scale dependence from observations and a high‐resolution coupled climate model. A dichotomy exists in the literature with respect to the sign of this term, that is, whether it is a source or a sink of EPE. We resolve this dichotomy by partitioning the SST and net heat flux into climatological mean, climatological seasonal cycle, and remaining transient contributions, thereby separating the mesoscale eddy variability from the forced seasonal cycle. In this decomposition the mesoscale air‐sea SST‐SHF feedbacks act as a 0.1 TW global sink of EPE. In regions of the ocean with a large seasonal cycle, for example, midlatitudes of the Northern Hemisphere, the EPE generation by the forced seasonal cycle exceeds the mesoscale variability sink, such that the global generation by seasonal plus eddy variability acts as a 0.8 TW source. EPE destruction is largest in the midlatitude western boundary currents due to mesoscale air‐sea interaction and in the tropical Pacific where SST variability is due mainly to the El Niño–Southern Oscillation. The EPE sink in western boundary currents is spatially aligned with SST gradients and offset to the poleward side of currents, while the mean and seasonal generation are aligned with the warm core of the current. By successively smoothing the data in space and time we find that half of the EPE sink is confined to timescales less than annual and length scales less than 2°, within the oceanic mesoscale band. Plain Language Summary: In this study we find that anomalous air‐sea interaction associated with ocean turbulence is responsible for removing potential energy from the global ocean circulation. This energy sink accounts for about 0.1 TW of energy that would otherwise be available for conversion from potential to kinetic energy of the anomalous flow field. It is found that the mean seasonal cycle is a source of potential energy and typically masks the sink associated with ocean turbulence. The sink of energy is locally confined to the strong midlatitude currents systems on the western side of ocean basins, such as the Gulf Stream in the North Atlantic and Kuroshio Extension in the North Pacific. The spatial locations of the sink point to possible future avenues for improving climate models by incorporating this sink, which is typically not resolved in standard climate models, and its subsequent impacts on the ocean circulation and future climate projections. Key Points: Air‐sea interaction at scales less than 2° and annual accounts for half of the global destruction of EPE The forced mean seasonal cycle is a source of available potential energy Mean and transient energy sinks are spatially offset and colocated with mean SSH and SST gradients, respectively